AB0484 Monotherapy with filgotinib, a jak1-selective inhibitor, reduces disease severity and alters immune cell subsets in the nzb/w f1 murine model of lupus. (12th June 2018) - Pohlmeyer, C.; Cui, Z.-H.; Han, P.; Clarke, A.S.; Jones, R.M.; Mollova, N.; Mikaelian, I.; Zaboli, S.; Shauf, A.; Di Paolo, J.A.
Abstract : Background: Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease characterised by immune system hyperactivation leading to the production of autoantibodies and immune attack on multiple organs including the skin and kidneys. High levels of type I interferons (IFNa/b) alter the activation state of immune cell populations and have been identified as a risk factor for SLE. Antibody blockade of the interferon alpha receptor (IFNAR) has demonstrated clinical efficacy in a Phase 2b study in SLE, and validates targeting this pathway in SLE 1 . Janus kinase 1 (JAK1) is critical for mediating downstream signalling of type I IFNs. Inhibition of JAK1, therefore, is anticipated to reduce IFN signalling, activation of immune cell subsets, and SLE disease activity. The JAK1 selective inhibitor filgotinib (FIL) is currently being evaluated in three proof-of-concept Phase 2 studies in SLE-like diseases. Objectives: To characterise the efficacy and mechanism-of-action of FIL in the NZB/W F1 spontaneous mouse model of lupus in a therapeutic setting. Methods: FIL was tested in the NZB/W F1 model of lupus at two concentrations (0.05% and 0.1%) formulated in chow and administered ad libitum from weeks 28–40. Cyclophosphamide (CP) was used as a positive control at 5 mg/kg, once daily, i.p. Efficacy was determined by changes in proteinuria, renal histopathology, and survival. Splenic cell populations were analysed by flow cytometry at study termination at week 40 to measure changes in immune cell subsets in diseased versus non-diseased mice and following FIL treatment. An in vitro murine whole blood pSTAT1 assay and PK exposure data were used to assess target coverage in the model. Results: In the NZB/W model, FIL showed a dose-dependent decrease in proteinurea with a concomitant reduction in BUN levels, renal inflammation, improved glomerular morphology, and increased survival (table 1). Diseased mouse spleens had decreased frequencies of naive T cells, increased frequencies of CD11 + dendritic cells (DCs), and an increased ratio of memory:naive T cells versus non-diseased mice. FIL treatment showed a dose-responsive reversal of these populations toward non-diseased levels. FIL inhibited in vitro IFNa-stimulated pSTAT1 signalling in T cells. Calculated JAK target coverage of pSTAT1 inhibition was similar to that observed in human studies at clinical doses. Conclusions: FIL demonstrated efficacy in the NZB/W F1 murine model of lupus with an alteration of splenic immune cell subsets affected by type I IFNs toward non-diseased levels. This data provides the basis for the evaluation of FIL as monotherapy in the currently ongoing Phase 2 studies in lupus-related diseases. Reference: [1] Furie R, et al. Arthritis Rheumatol2017;69:376–386. Disclosure of Interest: C. Pohlmeyer Shareholder of: Gilead Sciences, Inc, Employee of: Gilead Sciences, Inc, Z.-H. Cui Shareholder of: Gilead Sciences, Inc, Employee of: Gilead Sciences, Inc, P. Han Shareholder of: Gilead Sciences, Inc, Employee of: Gilead Sciences, Inc, A. Clarke Shareholder of: Gilead Sciences, Inc, Employee of: Gilead Sciences, Inc, R. Jones Shareholder of: Gilead Sciences, Inc, Employee of: Gilead Sciences, Inc, N. Mollova Shareholder of: Gilead Sciences, Inc, Employee of: Gilead Sciences, Inc, I. Mikaelian Shareholder of: Gilead Sciences, Inc, Employee of: Gilead Sciences, Inc, S. Zaboli Shareholder of: Gilead Sciences, Inc, Employee of: Gilead Sciences, Inc, A. Shauf Shareholder of: Gilead Sciences, Inc, Employee of: Gilead Sciences, Inc, J. Di Paolo Shareholder of: Gilead Sciences, Inc, Employee of: Gilead Sciences, Inc